(untitled) (Sotang, Yearly Peer Reviewed Journal, 2019)
Cultural diversity plays an important role in motivation and learning to the individuals. Effective learning depends on the learner’s motivations it depends on socio cultural environment. Such as learner’s age, sex, cast and ethnicity, religion, culture etc. This article reports how social and cultural diversity interplays on motivation and learning. The study was conducted based on library study and internet search. Articles related to interplays of cultural diversity in motivation and learning was reviewed extensively. Cultural diversity affects human behavior in the choice of a particular action, the persistence with it and the effort expended on it. It is an opportunity to gain various sources of knowledge. Cultural diversity helps to find out the cultural knowledge and skills to the learners and communicate with other ethnic groups. Multicultural knowledge is significant to make the learning motivational and respect the cultural diversity.